Arthrotomy versus arthroscopy in the treatment of the fragmented medial coronoid process of the ulna (FCP) in 421 dogs - Meyer-Lindenberg, A.; Langhann, A.; Fehr, M.; Nolte, I. (Veterinary and Comparative Orthopaedics and Traumatology, 2003)
In a retrospective trial over eight years 518 joints from 421 dogs with fragmented medial coronoid process of the ulna (FCP) were included. Seventy-five joints had an additional osteochondrosis dissecans of the medial aspect of the humeral condyle. Forty-six point eight percent of the dogs (197/421) were younger than one year. Two hundred and forty-seven joints were treated by conventional arthrotomy and 271 joints were treated by arthroscopy. Two hundred and thirty-eight cases (103 treated by arthrotomy and 135 by arthroscopy) were re-evaluated clinically and radiographically and 191 cases (88 treated by arthrotomy and 103 by arthroscopy) by means of a questionnaire at an average of 23 and 21 months after the operations, respectively. Forty-two point four percent (81/191) of the cases treated by arthrotomy did not show any lameness, 29.3% (56/191) showed temporary lameness after rest or heavy exercise, and 28.3% (54/191) showed constant lameness. The signs of which had, however, been reduced by surgery in 14 of these cases. Sixty point one percent (143/238) of the cases treated by arthroscopy did not show any lameness, 29.4% (70/238) showed temporary lameness after rest or heavy exercise and 10.5% (25/238) showed constant lameness, out of which four cases had improved after surgery. In the cases treated by arthroscopy, the period of convalescence was shorter. Differences between these methods were not observed with respect to the development of subsequent arthrosis. The results of the study show that arthroscopy, with its minimal invasive character, gives better functional results than conventional arthrotomy. However, the development of secondary arthrosis cannot be avoided by either method.
Keywords: FCP; dog; arthrotomy; arthroscopy; comparison